Assisted Reproductive Treatment Applications in Men With Normal Phenotype But 45,X/46,Xy Mosaic Karyotype: Clinical and Genetic Perspectives - Sevtap Kilic; Beril Yukse; Nicel Tasdemir; Muammer Dogan (Elsevier, 2010)
Objective: The 45,X/46,XY mosaic karyotype is expressed by a spectrum of genital phenotypes, ranging from normal males through to ambiguous genitalia and to normal females. Case Reports: We present three cases of men with azoospermia or severe oligozoospermia, and a 45,X/46,XY mosaic karyotype and two with a Y-chromosome microdeletion. Phenotypically, they appeared as normal males, with normal penis, scrotum and secondary sex characteristics. Testicular sperm extraction and aspiration were applied to patients, and couples were prepared for assisted reproductive therapy. All men with azoospermia or severe oligozoospermia were evaluated for karyotype and Y-chromosome microdeletion even if they had normal phenotypes. Conclusion: Possibilities for finding sperm and the biologic paternity in subjects with 45,X/46,XY karyotype should be considered. Furthermore, the increased risk for testicular neoplasia with mosaic karyotypes should be taken into consideration.